Introduction to the special issue 'The twin challenge of sustainability and digital transformation' - Wolfgang Gerstlberger; Gunnar Prause (Scientific Papers of the University of Pardubice, Series D: Faculty of Economics and Administration, 2024)
The interaction between the special issue and the sustainability of digital transformation have a special approach to circular economy models, blockchain, Industry 4.0, and legal frameworks. In addition, digital tools are discussed that really help in enhancing eco-efficiency and stakeholder involvement for sustainable business practices, considering challenges regarding scarcity of resources and policy alignment. The articles emphasize the importance of managerial attention, stakeholder collaboration, and interdisciplinary strategies in driving innovation and resilience across sectors. By integrating technological, regulatory, and cultural perspectives, this issue provides actionable insights for organizations to navigate the twin challenges of digitalization and sustainability, fostering a more sustainable and adaptive future.
Keywords: 330